Structured peer review: implementation and checklist development - Bahar Mehmani; Mario Malički (European Science Editing)
To address the low overlap between reviewer comments and the publication recommendations they make, as well as to suggest guidance on what kind of peer review report would benefit journals and editors the most, we introduced structured peer review to Elsevier journals and analyzed its effect in our June 2024 paper: peerj.com/articles/17514/ . To further promote the implementation of the structured peer review process and help reviewers prepare thorough review reports, in this paper, we present our set of structured peer review questions in a checklist format.